New Insights Into the Role of Inflammation in the Brain in Heart Failure - Badoer, Emilio (Frontiers in Physiology, 2022)
Heart failure is a growing medical problem. Although the underlying aetiology of heart failure differs according to the phenotype, there are some common characteristics observed in patients with heart failure. These include an increased sympathetic nerve activity, an activated renin-angiotensin system, and inflammation. The mechanisms mediating the increased sympathetic activity are not completely understood but the central nervous system plays a major role. Activation of the renin-angiotensin system plays an active role in the remodelling of the heart and in fluid and electrolyte imbalance. The presence of a central renin-angiotensin system means that locally produced angiotensin in the brain may also play a key role in autonomic dysfunction seen in heart failure. Markers of inflammation in the heart and in the circulation are observed in patients diagnosed with heart failure. Circulating proinflammatory cytokines can also influence cardiac function further afield than just locally in the heart including actions within the brain to activate the sympathetic nervous system. Preclinical evidence suggests that targeting the pro-inflammatory cytokines would be a useful therapy to treat heart failure. Most clinical studies have been disappointing. This mini review suggests that proinflammatory cytokines in the brain play a key role and there is a problem associated with access of effective doses of the drugs to the site of action in the brain. The recent advances in nanotechnology delivery techniques may provide exciting future technology to investigate the role of specific pro-inflammatory mediators as novel targets within the brain in the treatment of heart failure.